Report on industrial attachment with Molex Singapore Pte Ltd - Tan, Jian Hui (2015)
Concepts of Process Capability Study are discussed with an actual case study of Light Pipe Molding Tool Qualification. Said Light Pipe study itself is not a true representation of the process, due to the short-term nature of its sample collection. Thus, there is a need for a more complete study to substantiate the findings of the preliminary short-term study. Nonetheless, the gathered result is still useful for examining the subtleties of the capability study. The appreciation of the underlying principles is necessary for accurate assessments, and should be supplemented with exposure to diverse process conditions.